Dosimetric Evaluation and Clinical Application of Radioactive Iodine-125 Brachytherapy Stent in the Treatment of Malignant Esophageal Obstruction - Ji, Zhe; Yuan, Qianqian; Lin, Lei; Xing, Chao; Zhang, Xusheng; Yang, Sen; Jiang, Yuliang; Sun, Haitao; Zhang, Kaixian; Wang, Junjie (Frontiers in Oncology, 2022)
Objective: To evaluate the dosimetric characteristics and the clinical application of radioactive iodine-125 brachytherapy stent (RIBS) in malignant esophageal obstruction. Methods: The dose distribution of RIBS with different seed spacing, diameter and length was studied by treatment planning system (TPS) calculation, thermoluminescence dosimeter (TLD) measurement and Monte Carlo (MC) data fitting. And the data of esophageal cancer patients who were treat with this type of RIBS were analyzed retrospectively. Results: Doses around the RIBS calculated by the TPS lay between those measured by the TLDs and those simulated by the MC, and the differences between the three methods were significant (p<0.05), the overall absolute dose differences among the three methods were small. Dose coverage at 1.5 cm from the center was comprehensive when the activity reached 0.6 mCi. Both the conformability and the uniformity of isodose lines produced by a seed spacing of 1.0 cm were superior to those produced by a seed spacing of 1.5 cm. The data of 50 patients treated with RIBS were analyzed. They were followed up until February 2020 when all of the patients died. The overall improvement rate of dysphagia after RIBS implant was 90%. Moderate and severe complications with an incidence of more than 10% were hematemesis (28%), pain (20%), and lung infection (10%). Stent restenosis occurred in 4 patients at a median interval of 108 d from the procedure. The overall incidence of fatal complications was 38% (including hematemesis, infection and asphyxia). The median survival times of patients with and without a history of radiotherapy were 3.4 months and 6 months, respectively, the difference of which was significant (p=0.021). No other factors affecting survival were identified. For patients with and without a history of radiotherapy, the incidences of fatal complications were 51.7% and 19%, respectively (p=0.019). No correlation between dose and stent restenosis was found. Conclusion: TPS calculations are suitable for clinical applications. RIBS can effectively alleviate obstructive symptoms for patients with malignant esophageal obstruction, but the incidence of fatal complications was high, care should be taken when choosing this treatment.